Relative age-related differences between different competitive levels and field positions in young soccer players - Peña-González, I.; Javaloyes, A.; Sarabia, J. M.; Moya-Ramón, M. (Research in Sports Medicine, 2021)
The aims of this study were to report the relative age effect in different competitive levels and field positions and to analyse the differences within and between different competitive levels and field positions. Data for 203 young soccer players (14.2±1.1 years) included anthropometrics and physical performance (Countermovement jump [CMJ], 30-m sprint, T-test and Yo-Yo IR1). Their competitive level and their field position were registered. The percentage of relative older players (1stHY) was higher in the better competitive levels (L1: 80.6%, p <.001; L2: 68.2%, p <.001 and L3: 58.5%, p <.01), but it was similar between field positions (DF: 68.1%, p <.001; MF: 69.6%, p <.001 and FW: 67.2%, p <.001). Anthropometrical and physical performance differences were found between players of different competitive levels but not between relative older and younger players in each competitive level and field position. The relative age effect is higher in the better competitive levels. Anthropometrical and physical performance differences between players are not due to the relative age but to the level of competition. Relatively older players do not seem to be more likely to be selected for specific field positions. The causes of relative age effect need more research.